Modal phase-matched bound states in the continuum for enhancing third harmonic generation of deep ultraviolet emission - Abdelraouf, Omar A. M. (2024)
Coherent deep ultraviolet (DUV) light sources are crucial for various applications such as nanolithography, biomedical imaging, and spectroscopy. DUV light sources can be generated by using conventional nonlinear optical crystals (NLOs). However, NLOs are limited by their bulky size, inadequate transparency at the DUV regime, and stringent phase-matching requirements for harmonic generation. Recently, dielectric metasurfaces support high Q-factor resonances and offer a promising approach for efficient harmonic generation at short wavelengths. In this study, we demonstrated a crystalline silicon (c-Si) metasurface simultaneously exciting modal phase-matched bound states in the continuum (BIC) resonance at the fundamental wavelength of 840 nm with a higher degree of freedom for precise control of the BIC resonance and a plasmonic resonance at the wavelength of 280 nm in the DUV to enhance third harmonic generation (THG). We experimentally achieved a Q-factor of ∼180 owing to the relatively large refractive index of the c-Si and the geometric symmetry breaking of the structure. We realized THG at a wavelength of 280 nm with a power of 14.5 nW by using a peak power density of 15 GW/cm2 excitation. The measured THG power is 14 times higher than the state-of-the-art THG dielectric metasurfaces using the same peak power density in the DUV regime, and the maximum obtained THG power enhancement factor is up to 48. This approach relies on the significant third-order nonlinear susceptibility of c-Si, the interband plasmonic nature of the c-Si in the DUV, and the strong field confinement of BIC resonance to boost overall nonlinear conversion efficiency to 5.2 × 10-6% in the DUV regime. Our work shows the potential of c-Si BIC metasurfaces for developing efficient and ultracompact DUV light sources using high-efficacy nonlinear optical devices.